Kinematic Mapping in Semi-Euclidean 4-Space - Mehdi JAFARI (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
We study the some algebraic properties of matrix associated to Hamilton operators is defined for semi-quaternions. The kinematic mapping corresponding to these operators in semi-Euclidean 4-space is same as the kinematic mapping of Blaschke and Grünwald.Keywords: Hamilton operators, Quasi-elliptic geometry, Semi-quaternion